The Actin-Bundling Protein L-Plastin: A Critical Regulator of Immune Cell Function. (13th December 2011) - Morley, Sharon Celeste
Abstract : L-plastin is a leukocyte-specific protein that cross-links actin filaments into tight bundles, increasing the stability of actin-based structures such as podosomes and lamellipodia. While first identified as an abundant cytoplasmic protein in hematopoietically derived cells over 25 years ago, the requirement for L-plastin in multiple functions critical for immunity, such as antigen receptor signaling, adhesion, and motility, has only recently become clear. L-plastin has been identified as an important component in cellular processes critical for neutrophil, macrophage, osteoclast, eosinophil, and T- and B-lymphocyte biology. Following a brief description of the structure and function of L-plastin, the regulation of immune cell functions by L-plastin will be reviewed in detail.